2020
DOI: 10.1029/2019wr026381
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: A Comparison of Contemporary Practices of Riparian Buffer Retention Around Small Streams in Canada, Finland, and Sweden

Abstract: Forested riparian buffers are recommended to mitigate negative effects of forest harvesting on recipient freshwater ecosystems. Most of the current best practices of riparian buffer retention aim at larger streams. Riparian protection along small streams is thought to be lacking; however, it is not well documented. We surveyed 286 small streams flowing through recent clearcuts in three timber-producing jurisdictions-British Columbia, Canada (BC), Finland, and Sweden. The three jurisdictions differed in riparia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 50 publications
0
40
4
Order By: Relevance
“…Delineating the functional riparian area extent, however, is not a straightforward task and may require the understanding of local-scale environmental conditions since riparian functional attributes depend on sitespeci c variations such as landscape composition and environmental setting (Naiman and Décamps 1997). Given these challenges, riparian management projects have typically applied a " xed-width buffer guideline" (Kuglerová et al 2020). Unfortunately, xed-width buffers may ultimately fail in meeting management goals as they do not account for variations in site-speci c attributes (e.g., river slope and bank topography), and likely underestimate the full extent of riparian areas (Kuglerová et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Delineating the functional riparian area extent, however, is not a straightforward task and may require the understanding of local-scale environmental conditions since riparian functional attributes depend on sitespeci c variations such as landscape composition and environmental setting (Naiman and Décamps 1997). Given these challenges, riparian management projects have typically applied a " xed-width buffer guideline" (Kuglerová et al 2020). Unfortunately, xed-width buffers may ultimately fail in meeting management goals as they do not account for variations in site-speci c attributes (e.g., river slope and bank topography), and likely underestimate the full extent of riparian areas (Kuglerová et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…they were not measured in situ), inspection of GFC (Global Forest Change, loss-year data in 2001-2017) maps revealed no clear-cuts in the immediate vicinity (within 30 m) of any of the sampling sites. In addition, a recent survey of buffer management in Finland demonstrated that intact buffers around streams were on average 15 m wide (Kuglerová et al, 2020). The impairment of macroinvertebrate communities in small but not in large streams potentially reflects higher connectivity of headwater streams to their catchments (Gomi et al, 2002;Kuglerová et al, 2017) and/or dissipation of elevated nutrient and carbon concentrations towards downstream reaches (Futter et al, 2010;Schelker et al, 2014Schelker et al, , 2016.…”
Section: Discussionmentioning
confidence: 99%
“…For example, peatland drainage can elevate nutrient concentrations in recipient fluvial networks even 60 years after draining (Nieminen, Sallantaus, et al, 2017), whereas harvesting typically increases nutrients only for 5-10 years (Futter et al, 2016). Also, the negative effects of clearcutting alone are relatively manageable by retaining intact buffers between the stream and the harvested area (Kuglerová et al, 2020), whereas the impacts of forest harvest on drained peatlands are variable and extremely challenging to control .…”
Section: Introductionmentioning
confidence: 99%
“…While riparian buffers can come in many forms, which also brings different functionality (Kuglerová et al, 2020;Sonesson et al, 2020), all types of buffering imply some sort of limit to harvesting in the riparian zone. Limited logging and insufficient buffer width can still lead to changes in microclimatic conditions (Jyväsjärvi et al, 2020;Berrigan et al, 2021), which means that vegetation can also change in buffers.…”
Section: Forestrymentioning
confidence: 99%